EFEKTIVITAS “BIODERMA” SEBAGAI SOLUSI PENANGANAN LIMBAH DAN PENINGKATAN PRODUKSI TANAMAN JAGUNG - Gabrilliani Puspita Dewi; Brazilli Anastagia Silva; Jesxel Mulawanda Damanik; Yohanes Gaza Andri Orada; Miftah Lutfi Abdul Aziz; Rita Kurnia Apindiati (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
[THE EFFECTIVENESS OF "BIODERMA" AS A SOLUTION FOR WASTE HANDLING AND INCREASING CORN CROP PRODUCTION]. Each hectare of corn plantation can produce approximately 9 tons of corn and it is estimated that more than 2-3 tons of corn plant waste. This study aims to find innovations in the utilization of corn waste as fertilizer by using biochar enriched with Trichoderma sp. and Pseudomonas fluorescens. This research was conducted from June 2023 to September 2023 at the Plant Disease Laboratory, Faculty of Agriculture, Tanjungpura University. Corn planting distance was 50 cm x 20 cm with 5 treatments and 5 replications. Corn waste biochar enriched with Trichoderma sp. and P. fluorescens was named "Bioderma". Corn planting distance was 50 cm x 20 cm with 5 treatments and 5 replications. The treatments were 0 tons/ha, 5 tons/ha, 10 tons/ha, 15 tons/ha and 20 tons/ha. Data analysis used was analysis of variance (ANOVA) and continued with Duncan Multiple Range Test (DMRT) at the α = 5% level. The best response of corn plant growth with a Bioderma dose of 10 tons/ha. Bioderma application can increase plant height, stem diameter, number of leaves, fresh weight, and dry weight of corn plants.